A pedagogia da alternância no bacharelado em agronomia com ênfase em agroecologia e sistemas rurais sustentáveis (ProNERA/UFSCar): o campo e a universidade como territórios educativos - Sardo, Paola Maia Lo (2013)
This dissertation aims to analyze the pedagogical model used in a Bachelor of Agronomy offered to settled of the agrarian reform program, namely the alternation between school and community moments. The difficulty of the condensed subjects in the school time seems to be offset by the importance of the community time that provides local knowledge, through observation, analysis, and reflection, joining theory and practice, being pointed by the students as one of the reasons of higher learning. On community time, the greatest difficulties were balancing work with study and the lack of contact with the teachers. Moreover, the study ultimately allows the involvement of family, community and even the institutions for their development.